Association of quarterly prevalence of e‐cigarette use with ever regular smoking among young adults in England: a time–series analysis between 2007 and 2018. (9th March 2022) - Beard, Emma; Brown, Jamie; Shahab, Lion
Abstract: Aims: To assess how changes in the prevalence of e‐cigarette use among young adults have been associated with changes in the uptake of smoking in England between 2007 and 2018. Design: Time–series analysis of population trends with autoregressive integrated moving average with exogeneous input (ARIMAX models). Setting: England. Participants: Data were aggregated quarterly on young adults aged 16–24 years ( n  = 37 105) taking part in the Smoking Toolkit Study. Measures: In the primary analysis, prevalence of e‐cigarette use was used to predict prevalence of ever regular smoking among those aged 16–24. Sensitivity analyses stratified the sample into those aged 16–17 and 18–24. Bayes' factors and robustness regions were calculated for non‐significant findings [effect size beta coefficient (B) = 3.1]. Findings: There was evidence for no association between the prevalence of e‐cigarette use and ever regular smoking among those aged 16–24 [B = –0.015, 95% confidence interval (CI) = –0.046 to 0.016; P  = 0.341; Bayes factor (BF) = 0.002]. Evidence for no association was also found in the stratified analysis among those aged 16–17 (B = 0.070, 95% CI –0.014 to 0.155, P  = 0.102; BF = 0.015) and 18–24 (B = –0.021, 95% CI –0.053 to 0.011; P  = 0.205; BF = 0.003). These findings were able to rule out percentage point increases or decreases in ever regular smoking prevalence greater than 0.31% or less than −0.03% for 16–17‐year‐olds and 0.01 or −0.08% for 18–24‐year‐olds for every 1%‐point increase in e‐cigarette prevalence. Conclusion: Prevalence of e‐cigarette use among the youth population in England does not appear to be associated with substantial increases or decreases in the prevalence of smoking uptake. Small associations cannot be ruled out.